2000
DOI: 10.1073/pnas.97.22.12038
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of protein structures: Visualizing how a one-dimensional protein chain folds into a three-dimensional shape

Abstract: Here, we depict the anatomy of protein structures in terms of the protein folding process. Via an iterative, top-down dissecting procedure, tertiary structures are spliced down to reveal their anatomy: first, to produce domains (defined by visual three-dimensional inspection criteria); then, hydrophobic folding units (HFU); and, at the end of a multilevel process, a set of building blocks. The resulting anatomy tree organization not only clearly depicts the organization of a one-dimensional polypeptide chain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 44 publications
2
101
0
Order By: Relevance
“…8. Contact maps calculated for (a) the X-ray dihydrofolate reductase (DHFR) structure and the structures at the end of the simulation using (b) the three AS-DHFR fragments based on Gegg's cutting (Gegg et al 1997), and (c) the three DHFR fragments based on the Tsai et al (2000) cutting into building block algorithm. Each of the fragments is designated by the area enclosed by the rectangular box.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8. Contact maps calculated for (a) the X-ray dihydrofolate reductase (DHFR) structure and the structures at the end of the simulation using (b) the three AS-DHFR fragments based on Gegg's cutting (Gegg et al 1997), and (c) the three DHFR fragments based on the Tsai et al (2000) cutting into building block algorithm. Each of the fragments is designated by the area enclosed by the rectangular box.…”
Section: Discussionmentioning
confidence: 99%
“…The notation of the secondary structure used in this study is based on the Protein Data Bank (PDB; Bernstein et al 1977) Ala and Ser, respectively (in CPK rendering). The molecular dissection is based on the Gegg et al (1997) study and on the Tsai et al (2000) dissection algorithm (the cutting result can be viewed at our web site at http://protein3d.ncifcrf.gov/tsai/ anatomy.html. Six of the seven folded protein fragments used in the study are shown in red, green, and yellow in the two structures.…”
Section: Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Another approach to simplify the protein-folding problem is the building block folding model, in which protein fragments are produced either experimentally [101,102] or computationally [103][104][105][106]. Whether these fragments can form independent folding entities is further determined [107].…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%